Antropología aplicada, un caso particular: La Cabrera - Fernández Aparicio, Yolanda; Díaz Iglesias, Manuel (Estudios humanísticos. Geografía, historia y arte, 1989)
Whit this article we pretend to show the connection that exists among the antropology, the geography and the history and the rôle that they redeem in the adquisition of the concepts of space and time.